The Effectiveness Of A Multiliterate Learning Model To Improve Primary School Students' Critical Thinking Abilities In Science Subjects - Noke Widianingsih; Deni Kurniawan; Maman Rumanta (Universitas Muhammadiyah Enrekang, 2024)
The background to this research is the lack of maximum critical thinking skills of students in science learning in elementary schools. This research aims to analyze the increase in students' critical thinking skills and learning effectiveness after using the multiliteracy learning model. The method used is quasi-experimental with Nonequivalent Control Group Design. This research used a sample of 36 grade 5 students at SDN 254 Griya Bumi Antapani as an experimental class using a simple random sampling technique. The data collected to answer the research questions came from the pre-test and post-test which were carried out twice each at the 1st and 2nd meetings between the control class and the experimental class. The tests carried out are in the form of essay questions that have been validated by experts and are used to measure student learning outcomes that lead to critical thinking. Meanwhile, non-tests in the form of observations are useful for observing the effectiveness of student learning during the learning process. The treatment given is a multiliteracy learning model for the experimental class with adjusted syntax. Meanwhile, the control class uses a conventional model (lecture method). The results of this research show that the application of the multiliteracy learning model in science lessons after being tested using the t-test significance test shows that there are significant differences in 5 aspects of critical thinking for elementary school students as evidenced by the data from the control and experimental classes at meeting 1 which received an average score - 4.180 and at meeting 2 they got an average score of -6.814. This shows that the multiliteracy learning model is effective and significant in improving students' critical thinking skills in achieving success in the learning process and student learning outcomes in elementary schools.